Are mucocutaneous lesions seasonal in Behçet's disease? - Bilge Fettahlıoğlu Karaman (Cukurova Medical Journal, 2022)
Purpose: Although it is worth to investigate seasonality in a disease that has a recurrent course, this issue has not been dealt with sufficiently for Behçet’s disease. The aim of the study was to evaluate whether or not frequencies of its mucocutaneous attacks varied between months of the year. Materials and Methods: One hundred eight patients with Behçet’s disease were retrospectively evaluated in terms of attacks of oral aphthae, genital ulcers, and erythema nodosum. For their each visit, a four-week period preceded this visit and dates of attack onsets in this period were taken into consideration. Then, by using them, mean monthly attack numbers were calculated for time series analysis. Results: Although mean monthly attack numbers were higher in May and October for oral aphthae and in August for genital ulcers, seasonalities were not verified by time series analysis. Conclusion: After a literature search on PubMed, there is only one study that detected no seasonality for mucocutaneous lesions of Behçet’s disease, and only one study detected a seasonality for oral aphthae. However, it is worth noting that time series analysis is not utilized in these studies. Since the present study is retrospective, its results should be verified by diary-based prospective studies that include time series analysis.